1997
DOI: 10.1136/jnnp.62.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Is family history an independent risk factor for stroke?

Abstract: Conclusion-Genetic factors play a major part in the pathogenesis of subarachnoid haemorrhage, and family history of subarachnoid haemorrhage is the strongest independent risk factor for the disease. On the other hand, family history of intracerebral haematoma was not an independent risk factor for haematoma, but it might be a good predictor, which indirectly influences the pathogenesis of intracerebral haematoma via certain hereditary components such as hypertension, and even lifestyle factors such as alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…A recent Finnish study observed that a positive parental history of stroke was a predictor for the risk of stroke. 10 Kubota et al, 11 using a univariate analysis, showed that family history of subarachnoid hemorrhage and intracerebral hematoma was associated with an increased risk for each of these subtypes of stroke (ORϭ11.24 and ORϭ2.39, respectively), while family history of cerebral infarction was not a significant risk factor for developing stroke of this type. In a separate study, firstdegree relatives were found to have a risk almost 7 times higher than second-degree relatives of developing subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Finnish study observed that a positive parental history of stroke was a predictor for the risk of stroke. 10 Kubota et al, 11 using a univariate analysis, showed that family history of subarachnoid hemorrhage and intracerebral hematoma was associated with an increased risk for each of these subtypes of stroke (ORϭ11.24 and ORϭ2.39, respectively), while family history of cerebral infarction was not a significant risk factor for developing stroke of this type. In a separate study, firstdegree relatives were found to have a risk almost 7 times higher than second-degree relatives of developing subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Family history of stroke is perceived to be an important risk factor for stroke, but the importance of this risk factor has not been confirmed conclusively by epidemiological studies. [7][8][9][10][11][12][13][14][15][16][17] To further understand the genetic relationship between stroke and hypertension, we evaluated the aggregation of stroke in families prone to hypertension.…”
mentioning
confidence: 99%
“…Five case-control studies 41,48,50,63,64 recruited only patients aged Ͻ70 years, 1 study recruited patients with stroke onset at Ͻ65 years, 60 1 study recruited patients with stroke onset at Ͻ50 years, 55 and 1 study reported family histories separately for patients aged Ͻ54 and Ն54 years. 68 The combined OR for these younger patient groups was nonsignificantly (Pϭ0.10) higher (OR, 1.93; 95% CI, 1.7 to 2.2; PϽ0.00001; heterogeneity Pϭ0.0001; 1240 patients; Figure 6) than the remainder (OR, 1.69; 95% CI, 1.6 to 1.8; PϽ0.00001; heterogeneity Pϭ0.00001).…”
Section: Influence Of Agementioning
confidence: 99%
“…Data for hypercholesterolemia were conflicting. Thrift et al 34 found a negative association; Giroud et al 16 found no association; and Zodpey et al 20 and Kubota et al 17 found a positive association for hypercholesterolemia. The difference might be explained by the use of different definitions of hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 98%
“…13,16,17,20,23,26,28,30 The overall OR crude was 1.27 (95% CI, 0.98 to 1.65) (Figure 4). Leppälä et al 7 reported on diabetes and risk of ICH; the RR adjusted was 1.64 (95% CI, 0.77 to 3.51).…”
Section: Diabetes Mellitusmentioning
confidence: 99%